2020
DOI: 10.1002/ecs2.3312
|View full text |Cite
|
Sign up to set email alerts
|

Spotted owls and forest fire: Comment

Abstract: v Volume 11(12) v Article e03312 COMMENT JONES ET AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Finally, the lack of consistency among Humboldt marten studies is suggestive of imperfect knowledge of what components constitute Humboldt marten habitat. To avoid differing views for rare species conservation (e.g., Gutiérrez, 2020 ; Jones et al, 2020 ), amassing information collaboratively with a goal of prospective meta-analyses and study-level replication will be essential ( Facka & Moriarty, 2017 ; Nichols, Kendall & Boomer, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the lack of consistency among Humboldt marten studies is suggestive of imperfect knowledge of what components constitute Humboldt marten habitat. To avoid differing views for rare species conservation (e.g., Gutiérrez, 2020 ; Jones et al, 2020 ), amassing information collaboratively with a goal of prospective meta-analyses and study-level replication will be essential ( Facka & Moriarty, 2017 ; Nichols, Kendall & Boomer, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, counter-evidence reviewed here was used to support contentious conclusions in a metaanalysis of the impacts of high-severity fire on California Spotted Owls (Strix occidentalis occidentalis; Lee 2018). The authors of many of the studies included in that meta-analysis subsequently demonstrated methodological weaknesses in the meta-analysis that undermine those conclusions (Jones et al 2020a). Unwarranted uncertainty about the use of high-severity burn areas by California Spotted Owls (Jones et al 2019, Peery et al 2019 has detrimentally impacted the management of this sensitive species (Stephens et al 2019, Jones et al 2020b.…”
Section: Conclusion and Management Implicationsmentioning
confidence: 99%
“…The authors of many of the studies included in that meta‐analysis subsequently demonstrated methodological weaknesses in the meta‐analysis that undermine those conclusions (Jones et al. 2020 a ). Unwarranted uncertainty about the use of high‐severity burn areas by California Spotted Owls (Jones et al.…”
Section: Conclusion and Management Implicationsmentioning
confidence: 99%
“…I evaluated 4 of the most important papers in the ongoing scientific conflict over spotted owls and forest fire, 2 from each side of the issue (Bond et al, 2009; Jones et al, 2016; Jones et al, 2020; Lee, 2020). Forest fire is a natural disturbance event (Marlon et al, 2012) and prominent management issue that can affect habitat of spotted owls, a species that has driven many forest-management decisions over the past few decades (Weatherspoon et al, 1992; USDA, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Forest fire is a natural disturbance event (Marlon et al, 2012) and prominent management issue that can affect habitat of spotted owls, a species that has driven many forest-management decisions over the past few decades (Weatherspoon et al, 1992; USDA, 2018). In summary, Bond and Lee claim/argue/have concluded that wildfire is not a threat to spotted owl population persistence so logging should not be used to alter vegetation in spotted owl habitat, while Jones et al claim/argue/have concluded wildfire harms spotted owls, so logging spotted owl habitat to reduce fire severity and extent is justified (Jones et al, 2020).…”
Section: Methodsmentioning
confidence: 99%